CRISIS MANAGEMENT OF HUNGARIAN TOURIST ATTRACTIONS BEFORE AND DURING THE CORONAVIRUS CRISIS - Krisztina Keller; Nikoletta Kaszás; Szabolcs Mátyás (Acta Economica)
The aim of the study is to examine how the crisis management of tourist attraction sites evolved before and during the coronavirus epidemic. Eighty-seven in-depth interviews were conducted with managers responsible for crisis management of attraction sites, examining the stages of preparation and response regarding the perception of the crisis, setting up a crisis plan and crisis team, defining priorities and measures during the coronavirus pandemic, and the lessons learned. Results have demonstrated that most had neither a crisis management plan nor experience gained from previous crises. Most of the enterprises set up a business management team consisting of managers, which then defined the retention of the workforce as a primary priority, while the steps that were taken mainly related to working from home and the use of public wage subsidies, as well as a rethinking of communication.